Design and fabrication of three shelves book trucks - Muhamad Muhaimin, Roni (2009)
The main objective of this project is to design and fabricate of three shelves book trucks which can make people easy in doing their daily job. Purpose of this shelves produced is to make a transportation of books, reference materials, medical charts and others materials more easy from a place to another. With application of wheel, holder and barrier at the main part, this shelves book trucks can accept at minimum two hundred (200) to three hundred (300) of books and others. Assume of the materials have been done by consider the maximum size is three to four centimetre (cm). Currently, the product that exist in the market not meet customer need, that’s why this product produced to make customer not hesitate to use it. Three shelves book trucks produced by selection the suitable materials, techniques and process which is can make the product have long-life span and can detain the load given. The ideas to produced this product is based on student’s creativity. Besides, the design that have been selected base on stability, affordable to accept load and also ability to bring anywhere because of the size and the function. There are several process that used during fabricate this product and it’s entertain in this report.